2014
DOI: 10.1038/cddis.2014.182
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol targets proteostasis and acts synergistically with a heat-shock protein 90 inhibitor to kill human glioblastoma cells

Abstract: Glioblastoma multiforme is a devastating disease of the central nervous system and, at present, no effective therapeutic interventions have been identified. Celastrol, a natural occurring triterpene, exhibits potent anti-tumor activity against gliomas in xenograft mouse models. In this study, we describe the cell death mechanism employed by celastrol and identify secondary targets for effective combination therapy against glioblastoma cell survival. In contrast to the previously proposed reactive oxygen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 67 publications
2
37
0
2
Order By: Relevance
“…47,48 Compound 2 (celastrol) has been reported to have activity against osteosarcoma, head and neck cancer, and glioblastoma. 4951 Additionally, both compounds 1 and 2 have been reported to have activity against lung and prostate cancer cell lines through a variety of mechanisms. Compound 1 was reported to inhibit A549 and PC3 cell growth through glutathione depletion mechanisms, 52,53 while 2 inhibited A549 cells through activation of mitochondrial and Fas/FasL (Fas receptor/Fas ligand) apoptotic pathways and to have activity against DU145 prostate cancer cells via an hERG-dependent mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…47,48 Compound 2 (celastrol) has been reported to have activity against osteosarcoma, head and neck cancer, and glioblastoma. 4951 Additionally, both compounds 1 and 2 have been reported to have activity against lung and prostate cancer cell lines through a variety of mechanisms. Compound 1 was reported to inhibit A549 and PC3 cell growth through glutathione depletion mechanisms, 52,53 while 2 inhibited A549 cells through activation of mitochondrial and Fas/FasL (Fas receptor/Fas ligand) apoptotic pathways and to have activity against DU145 prostate cancer cells via an hERG-dependent mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Celastrol exhibits selective cytotoxic effect and mobilizes cytosolic calcium towards EGFR mutant NSCLCs. The natural triterpenoid compound celastrol is a promising cytotoxic agent in a great variety of cancer models (17)(18)(19)(20). It was previously reported that celastrol has the potency to combat gefitinib-resistant NSCLCs by inducing apoptosis through caspase-dependent pathways and Hsp90 client protein degradation.…”
Section: Resultsmentioning
confidence: 99%
“…ise gliom hücrelerinde celastrol uyarımı ile meydana gelen paraptozisin apoptozdan bağımsız olarak meydana geldiğini göstermişlerdir. 32 Bu bağlamda celastrolün paraptozdan ziyade, hücresel şartlara ve hücre tiplerine bağlı olarak farklı hücre ölüm şekillerini uyarabileceği söylenebilmektedir.…”
Section: Celastrolün Anti̇kanser Etki̇si̇unclassified